2010
DOI: 10.1007/s00018-010-0390-y
|View full text |Cite
|
Sign up to set email alerts
|

Glial versus melanocyte cell fate choice: Schwann cell precursors as a cellular origin of melanocytes

Abstract: Melanocytes and Schwann cells are derived from the multipotent population of neural crest cells. Although both cell types were thought to be generated through completely distinct pathways and molecular processes, a recent study has revealed that these different cell types are intimately interconnected far beyond previously postulated limits in that they share a common post-neural crest progenitor, i.e. the Schwann cell precursor. This finding raises interesting questions about the lineage relationships of hith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 149 publications
2
41
0
Order By: Relevance
“…At this point, SCPs can be considered as bipotent cells that chose their final fate depending on interactions with the growing nerves. Nerve-derived Neuregulin1 (3,9) or other yet unknown signals could stimulate gliogenesis via Foxd3, a possibility that remains to be tested. In contrast to presumptive SCs, hypaxial melanocytes stemming from the SCP population down-regulate Foxd3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At this point, SCPs can be considered as bipotent cells that chose their final fate depending on interactions with the growing nerves. Nerve-derived Neuregulin1 (3,9) or other yet unknown signals could stimulate gliogenesis via Foxd3, a possibility that remains to be tested. In contrast to presumptive SCs, hypaxial melanocytes stemming from the SCP population down-regulate Foxd3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The origins of pigment cells, their ancestral relationship to additional NC derivatives, and the mechanisms by which they segregate from each other remain poorly understood. Research in these areas is of fundamental importance for understanding aspects of pigment cell development as well as of adult physiology and pathology (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SCPs are believed to be a transient cell population formed during development from NCCs of the ventral migratory pathway in the trunk that can differentiate into Schwann cells. Within the nerves, neuregulin 1 inserted into the axonal membrane of motor and sensory neurons promotes a glial and inhibits a melanocyte fate, whereas insulin-like growth factor (IGF) and platelet-derived growth factor (PDGF) produced by maturing Schwann cells promote a melanocyte fate of SCPs in the nerves (Adameyko and Lallemend, 2010;Adameyko et al, 2009;Ernfors, 2010). However, the origin of melanocytes in the head region has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, attenuating expression of the melanocyte regulator microphtalmia-associated transcription factor (MITF) in culture facilitated the advent of glial markers (Thomas and Erickson, 2008;Thomas and Erickson, 2009). In addition, in vivo analysis showed that a late subset of melanocytes is normally produced from an initial population of Schwann cell precursors (Adameyko et al, 2009), and some diseases of the NC-derived nervous system are frequently associated with abnormal pigmentation (Adameyko and Lallemend, 2010).…”
Section: Introductionmentioning
confidence: 99%